Floristic diversity and standing stock of timber in homegardens of Thrissur district, Kerala - Unnithan, S.R.; Kunhamu, T.K.; Sunanda, C.; Anoop, E.V.; Jamaludheen, V.; Santhoshkumar, A.V. (Indian Journal of Agroforestry, 2020)
A field study was conducted to investigate the present status in terms of floristic diversity and standing stock of timber in the traditional home gardens of Kerala with focus on Thrissur district. The study involved two stage stratified sampling of home gardens from 10 panchayaths located in the highland, midland, coastal and extra one peri-urban region of the Thrissur district. A total of 330 home gardens were sampled as part of the study. About 163 plant species were recorded from all the sampled home gardens of Thrissur district that included 122 trees species and 41 agricultural crop species. A consistent decline in species diversity with decrease in home garden size was observed. Most abundant functional group of trees found in surveyed home gardens were timber species (53 species), followed by fruit trees (39 species). A sharp decline in number of species was observed in coastal land and peri-urban areas. Total standing stock of prominent timber tree species were in the order Mangifera indica (38,62,996.9 m3), Tectona grandis (32,22,392.9 m3) and Artocarpus heterophyllus (30,28,362.2 m3). Average standing stock and projected standing stock of all timber species for the entire Thrissur district were 55.12 m3ha-1 and 166,85,096.4 m3, respectively. To sum up, though the standing stock remained unaffected, the patterns of species composition and functional diversity of home gardens in Thrissur district are under change indicating their declining dependence for livelihood and economic security.